Direct Z-scheme FeVO4/BiOCl heterojunction as a highly efficient visible-light-driven photocatalyst for photocatalytic dye degradation and Cr(VI) reduction - Auttaphon Chachvalvutikul (2020)
In this work, potential applications of a direct Z-scheme FeVO4/BiOCl heterojunction for photocatalytic degradation of organic dyes (methylene blue, MB and rhodamine B, RhB) and reduction of hexavalent chromium (Cr(VI)) ion under visible light irradiation were reported. Firstly, FeVO4 and BiOCl were synthesized by using a microwave heating method. Then, the FeVO4/BiOCl nanocomposites with different weight percentages of FeVO4 (1, 3, 6.25, 12.5 and 25%wt) were fabricated by a method of modified wet impregnation. The photocatalytic degradation activities of the nanocomposites were investigated in parallel with pure BiOCl and FeVO4. Among the as-prepared nanocomposites, the FeVO4/BiOCl nanocomposite with 6.25%wt of FeVO4 exhibited the highest photocatalytic dye degradation efficiency; 99.8% of RhB was degraded after being irradiated for 360 min, while 87.2% of MB was degraded. Similarly, this nanocomposite photocatalytically reduced 97.8% of Cr(VI) at a pH value of 3. The superior photocatalytic activity can be ascribed to the effective visible light absorption of the FeVO4/BiOCl heterojunction and the suppression of the recombination process of photogenerated electron-hole pairs. Additionally, the improved charge migration and separation efficiencies between FeVO4 and BiOCl through the direct Z-scheme charge transfer pathway are involved, as evidenced by the trapping experiments, and the UV-visible diffuse reflectance (UV-vis DRS), photoluminescence spectroscopy (PL) and electrochemical impedance spectroscopy analyses. Photocatalytic mechanisms of the direct Z-scheme FeVO4/BiOCl heterojunction for the photodegradation of RhB and photoreduction of Cr(VI) have been proposed and discussed in greater detail.